2019
DOI: 10.1096/fj.201802502r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an intrinsic lysophosphatidic acid acyltransferase activity in the lipolytic inhibitor G 0 /G 1 switch gene 2 (G0S2)

Abstract: G0/G1 switch gene 2 (G0S2) is a specific inhibitor of adipose triglyceride lipase (ATGL), the rate‐limiting enzyme for intracellular lipolysis. Recent studies show that G0S2 plays a critical role in promoting triacylglycerol (TG) accumulation in the liver, and its encoding gene is a direct target of a major lipogenic transcription factor liver X receptor (LXR)α. Here we sought to investigate a lipolysis‐independent role of G0S2 in hepatic triglyceride synthesis. Knockdown of G0S2 decreased hepatic TG content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…HILPDA and G0S2 share extensive sequence homology, and both proteins are able to inhibit ATGL. Recently, evidence was provided that G0S2 not only suppresses lipolysis but also promotes triglyceride synthesis by carrying glycerol-3-phosphate acyltransferase (GPAT/LPAAT/AGPAT) enzymatic activity [ 39 ]. Given the very small size of HILPDA (63 amino acids), it is unlikely that HILPDA can itself function as a fatty acid esterification enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…HILPDA and G0S2 share extensive sequence homology, and both proteins are able to inhibit ATGL. Recently, evidence was provided that G0S2 not only suppresses lipolysis but also promotes triglyceride synthesis by carrying glycerol-3-phosphate acyltransferase (GPAT/LPAAT/AGPAT) enzymatic activity [ 39 ]. Given the very small size of HILPDA (63 amino acids), it is unlikely that HILPDA can itself function as a fatty acid esterification enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the G 0 S 2 gene is upregulated by the lipogenic transcription factor liver X receptor α. 7 In addition, the G 0 S 2 gene has been found to be hypermethylated in certain types of cancer, indicating a possible role in cancer development. 4 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…This study showed that G0S2 is a component for regulation in lipolysis, implicating it as potential target in the treatment of obesity and diabetes related conditions such as NAFLD [12][13][14]. Other studies have revealed several additional potential functions of G0S2 in lymphocyte activation, proliferation of leukemia cells, promotion of apoptosis, and reduction of tumor growth [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 64%